Drying of the Martian mesosphere during aphelion induced by lower temperatures - Daniel Toledo; Pascal Rannou; Victor Apéstigue; Raul Rodriguez-Veloso; Ignacio Arruego; German Martínez; Leslie Tamppari; Asier Munguira; Ralph Lorenz; Aurélien Stcherbinine; Franck Montmessin; Agustin Sanchez-Lavega; et al. (Communications Earth & Environment)
Abstract The formation of water ice clouds or hazes on Mars imposes substantial limitations on the vertical transport of water into the middle-upper atmosphere, impacting the planet’s hydrogen loss. Recent observations made by the Mars Environmental Dynamics Analyzer instrument onboard Mars 2020 Perseverance rover have shown a marked decline in water ice abundance within the mesosphere (above 35-40 km) when Mars is near its aphelion (near the northern summer solstice), notably occurring during solar longitudes (Ls) between Ls 70∘ and 80∘. Orbital observations around the same latitudes indicate that temperatures between  ~ 30-40 km reach a minimum during the same period. Using cloud microphysics simulations, we demonstrate that this decrease in temperature effectively increases the amount of water cold-trapped at those altitudes, confining water ice condensation to lower altitudes. Similarly, the reinforcement of the cold trap induced by the lower temperatures results in significant reductions in the water vapor mixing ratio above 35–40 km, explaining the confinement of water vapor observed around aphelion from orbiters.